Prevalence and predictors of risk factors for Brucellosis. (2016)
Introduction. Brucellosis is endemic in Nigeria and risk factors enhancing its transmission are prevalent. Methods. Following serological evidence of brucellosis and isolation of B. abortus from slaughtered cattle in Ibadan, Nigeria, we administered a semi-structured questionnaire to determine the prevalence and predictors of eating and selling bovine gravid uterus among 350 meat handlers from five major meat processing facilities. We conducted key informant interview for five leading traditional healers to document its use. Data were analyzed using Stata 12. Results. The prevalence of eating and selling gravid uterus were 29.7% and 40.3% respectively. Being meat/offal processor (OR=1.9, 95%CI: 1.11-3.3, P = 0.008) and not knowing that eating undercooked contaminated gravid uterus could expose humans to brucellosis (OR=19.5; 95%CI: 5.73-66.03; P = 0.000) were strong predictors of eating gravid uterus. Similarly, being adult (OR = 1.7, 95%CI: 1.08-2.57, P = 0.02) and inadequate knowledge of brucellosis as a preventable disease (OR = 0.03; 95%CI: 0.004-0.27, P = 0.001) predicted selling gravid uterus. Qualitative data from the traditional healers revealed using gravid uterus as special medicinal preparations to hasten parturition in overdue pregnancies, treat infertility and old age diseases in humans. Conclusions. We demonstrated a high prevalence of risk factors for brucellosis transmission, and some meat handlers’ sociodemographic characteristics and brucellosis knowledge-based markers as predictors of these factors. The traditional healers’ practices portend a challenge to the current brucellosis control strategy. These findings provide insights into designing all-inclusive health programmes aimed at controlling brucellosis spread in Nigeria and other similar settings in developing countries.